Komparasi Problem Posing dan Solving terhadap Kemampuan Berpikir Kritis Ditinjau dari Self Confidence - Egy Purwanda; Ahmad Yani T; Utin Desy Susiaty (SAP (Susunan Artikel Pendidikan), 2020)
The purpose of this study is to look at the comparison of Problem Posing and ProblemSolving learning models towards critical thinking skills in terms of students' Self Confidence in the function material. The research method is an experiment, in the form of a Quasi Experiment Design, with a 2x3 factorial design. The study population was all eighth-grade students of SMP Negeri 3 SanggauLedo TA. 2019/2020 which consisted of 3 classes, that used the Cluster Random Sampling technique. The data analysis technique of the variance analysis of the two cell roads was not the same and it was concluded that (1) the Problem Posing learning model provided better critical thinking skills than Problem Solving; (2) students with high, medium and low self-confidencehad the same critical thinking skills; (3) in each learning model, students with high, medium and low self-confidencehad the same critical thinking skills; (4) in each category of students' self-confidence, the Problem Posing learning model provided better critical thinking skills than Problem Solving.